Inflammatory biomarkers in Alzheimer's disease plasma. Issue 6 (29th April 2019) - Morgan, Angharad R.; Touchard, Samuel; Leckey, Claire; O'Hagan, Caroline; Nevado‐Holgado, Alejo J.; ,; Barkhof, Frederik; Bertram, Lars; Blin, Olivier; Bos, Isabelle; Dobricic, Valerija; Engelborghs, Sebastiaan; et al.
Abstract: Introduction: Plasma biomarkers for Alzheimer's disease (AD) diagnosis/stratification are a "Holy Grail" of AD research and intensively sought; however, there are no well‐established plasma markers. Methods: A hypothesis‐led plasma biomarker search was conducted in the context of international multicenter studies. The discovery phase measured 53 inflammatory proteins in elderly control (CTL; 259), mild cognitive impairment (MCI; 199), and AD (262) subjects from AddNeuroMed. Results: Ten analytes showed significant intergroup differences. Logistic regression identified five (FB, FH, sCR1, MCP‐1, eotaxin‐1) that, age/APOε4 adjusted, optimally differentiated AD and CTL (AUC: 0.79), and three (sCR1, MCP‐1, eotaxin‐1) that optimally differentiated AD and MCI (AUC: 0.74). These models replicated in an independent cohort (EMIF; AUC 0.81 and 0.67). Two analytes (FB, FH) plus age predicted MCI progression to AD (AUC: 0.71). Discussion: Plasma markers of inflammation and complement dysregulation support diagnosis and outcome prediction in AD and MCI. Further replication is needed before clinical translation.